Dependence of blistering and deuterium retention on damage depth in damaged tungsten exposed to deuterium plasma. (13th April 2021) - Wang, Shiwei; Guo, Wangguo; Cheng, Long; Schwarz-Selinger, Thomas; Liu, Mi; Zhu, Xiuli; Yuan, Yue; Fu, Engang; Lu, Guang-Hong
Abstract: The effect of different damage depth on blistering and deuterium (D) retention has been investigated in heavy-ion-damaged tungsten (W) with exposure to D plasma (40 eV, 1 × 10 22 ions m −2 s −1 ) at 550 K. Different damage depths are realized via copper (Cu) ion irradiation with energies of 1, 3, and 6 MeV on W samples with the same calculated peak damage level of 0.5 dpa. The plasma-induced blister density reduces with increasing damage depth, which is explained based on the recently proposed dislocation nucleation mechanism of blistering. Comparison of D retention measured by nuclear reaction analysis (NRA) and thermal desorption spectroscopy (TDS) reveals that retention at depths larger than 7.4 μ m—which is far beyond the ion damage depth—increases with damage depth. Such a phenomenon indicates a gradual increase of diffusion flux inside the damaged sample with the increasing damage depth. It is suggested that it originates from the observed difference in blister density. Besides the widely acknowledged enhanced D retention due to ion damage, this work shows a strong impact of the damage depth on blistering such as the blister density, and by which the D diffusion flux inside W and total D retention are further affected.